SASTRA LISAN DI KECAMATAN DONDO KABUPATEN TOLITOLI (KAJIAN EKOKRITIK) - Taufik, Taufik; Lembah, Gazali; Kangiden, Nurhaya (BAHASANTODEA, 2017)
The problem of this reseach are: 10 how is the existence of oral literaly ecolagy in Dondo Sub-district Tolitoli regency? 2) How is the form of oral literature (its relation to the environment) ekolagy in Dondo Sub-district Tolitoliregency? This reseach intenst to discribe the existence of oral literature ecology and form of oral literature. The reseach result of the existece of oral literaly in ethnic Dondo relate to the environment reveals that there are several literaly-styl stories in the form of legens: legend of Toga lake, legen of tando Tugan, legen of Sanjangan lake, epik of lanoni. Myth: Nunue (Bayan Tree), Antulan and Karampua, prohibition in trowing oil to the soil or hot water to the ground, cooking vegetables that have segmens, and wash laundry of menstruation to the rive. Literature that is not a story sad funeral song, chid cradle singing, customary rule of Ogo Menambu (draw water), and Mesusian (Petition), legesan (poem), and tatangki (Puzzel).